OPTIMUM CONDITIONS FOR PHENYLALANINE AMMONIA LYASE EXTRACTION AND PURIFICATION FROM LOCALLY CULTIVATED GRAPE SEEDS - S. Y. Hadeel,; S. A. Khalida, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
In the present study, Phenylalanine ammonia lyase (PAL) activity was detected in different parts of grape plant (leaves, pulp, whole seeds and defatted seeds) extracts. The results revealed that the whole seed possess highest PAL activity (69.44 U), followed by defatted seed (44.22 U), whereas extracts of leaves and pulp gave the lowest activity values (22.77 and 5.11 U, respectively). The optimum conditions for crude PAL extraction achieved using 50mM potassium phosphate buffer (pH 7) at mixing ratios of (1:7) for 1 h. extraction time. PAL was shown to precipitate out at the saturation range between 20-90%. For further purification, gel filtration chromatography using Sephadex G-200 column (1.5×70) and ion exchange chromatography using DEAE- Cellulose (DE 52) column (3.2× 10) were applied. The specific activity, number of folds and yield of purified PAL was 1157 U/mg, 19.94 and 15.32 % respectively.